SECURITY PRIVACY & SPIES. - Vance, Roger L. (American History, 2016)
The article discusses the invoking of a 1797 U.S. law by the Federal Bureau of Investigation (FBI) to require Apple technology company to write software that will disable encryption protections on the iPhone smartphone. Emphasis is given to topics such as the balance between privacy and security, the role of spies and espionage in war, and access of personal data.